2022
DOI: 10.3390/plants11060773
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Lotusine on Solar UV-Induced Matrix Metalloproteinase-1 Expression

Abstract: Solar ultraviolet (sUV) radiation remains a major cause of skin aging. Nelumbo nucifera (lotus) is a well-known edible plant widely grown in Asia, including Korea, China, and Japan. The lotus consists of flowers, leaves, stems, and seeds, and all parts reportedly possess nutritional and medical values. Traditionally, lotus flowers, leaves, stems, and seeds have been used as antidiarrheal agents, diuretics, antipyretics, and antimicrobial and antihyperlipidemic agents. In addition, the Nelumbo nucifera lotus em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Effects of Q-3-GR on MAPK/AP-1 signaling pathway in UVAirradiated HDFn cells The MAPK signaling pathway is stimulated by ROS, resulting in activation of the AP-1 transcription factor, and formation of the c-Fos and c-Jun heterodimer complex. Activated AP-1 stimulates the production of MMPs, which in turn induces collagen degradation [24,25]. Thus, we performed western blotting to investigate the effect of Q-3-GR on the MAPK/AP-1 signaling pathway.…”
Section: Effects Of Q-3-gr On Procollagen Type I Expression In Uvairr...mentioning
confidence: 99%
“…Effects of Q-3-GR on MAPK/AP-1 signaling pathway in UVAirradiated HDFn cells The MAPK signaling pathway is stimulated by ROS, resulting in activation of the AP-1 transcription factor, and formation of the c-Fos and c-Jun heterodimer complex. Activated AP-1 stimulates the production of MMPs, which in turn induces collagen degradation [24,25]. Thus, we performed western blotting to investigate the effect of Q-3-GR on the MAPK/AP-1 signaling pathway.…”
Section: Effects Of Q-3-gr On Procollagen Type I Expression In Uvairr...mentioning
confidence: 99%
“…Few studies have been reported on the biological activity of the benzyltetrahydroisoquinoline alkaloid lotusine. It has potential cardiac protective activity against doxorubicin-induced oxidative stress [ 22 ] and alleviates UV-induced expression of MMP-1 in skin keratinocytes, thus having potential anti-wrinkle effects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%